Temporal oculomotor inhibition of return and spatial facilitation of return in a visual encoding task - Luke, Steven G.; Schmidt, Joseph; Henderson, John M. (Frontiers in Psychology, 2013)
Oculomotor inhibition of return (O-IOR) is an increase in saccade latency prior to an eye movement to a recently fixated location compared to other locations. It has been proposed that this temporal O-IOR may have spatial consequences, facilitating foraging by inhibiting return to previously attended regions. In order to test this possibility, participants viewed arrays of objects and of words while their eye movements were recorded. Temporal O-IOR was observed, with equivalent effects for object and word arrays, indicating that temporal O-IOR is an oculomotor phenomenon independent of array content. There was no evidence for spatial inhibition of return. Instead, spatial facilitation of return was observed: Participants were significantly more likely than chance to make return saccades and to refixate just-visited locations. Further, the likelihood of making a return saccade to an object or word was contingent on the amount of time spent viewing that object or word before leaving it. This suggests that, unlike temporal O-IOR, return probability is influenced by cognitive processing. Taken together, these results are inconsistent with the hypothesis that inhibition of return functions as a foraging facilitator. The results also provide strong evidence for a different oculomotor bias that could serve as a foraging facilitator: saccadic momentum, a tendency to repeat the most recently executed saccade program. We suggest that models of visual attention could incorporate saccadic momentum in place of inhibition of return.